12-month patterns of serum markers of collagen synthesis, transforming growth factor and connective tissue growth factor are similar in new-onset and chronic dilated cardiomyopathy in patients both with and without cardiac fibrosis. (August 2017) - Rubiś, Paweł; Wiśniowska-Smiałek, Sylwia; Wypasek, Ewa; Rudnicka-Sosin, Lucyna; Hlawaty, Marta; Leśniak-Sobelga, Agata; Kostkiewicz, Magdalena; Podolec, Piotr
Highlights: Kinetics of collagen type I and III synthesis in DCM move in opposite directions. Production of collagen type I increases but collagen type III decreases. TGF and CTGF levels over 12-month follow-up had a tendency to decrease. Regardless of DCM duration or fibrosis, kinetics of fibrosis markers were similar. Improved understanding of fibrosis may translate into tailored therapy. Abstract: Background: The dynamics of the extracellular matrix (ECM) fibrosis process in dilated cardiomyopathy (DCM) may be assessed non-invasively by means of serum markers of fibrosis. Aim: To explore the kinetics of serum markers of fibrosis during a 12-month follow-up in DCM. Methods: We included 70 consecutive DCM patients (pts) (48 ± 12.1 years, EF 24.4 ± 7.4%) with new-onset (n = 35, duration <6 months) and chronic DCM (n = 35, >6 months). Markers of collagen type I and III synthesis – procollagens type I and III carboxy- and amino-terminal peptides (PICP, PINP, PIIICP, PIIINP), and ECM metabolism controlling factors – tumor growth factor beta-1 (TGF1-β), and connective tissue growth factor (CTGF) – were measured in serum at baseline, and at 3- and 12-month follow-up. All pts underwent endomyocardial biopsy to determine the presence and extent of ECM fibrosis. Results: Markers of collagen type I synthesis (PICP and PINP) were almost homogenously increased over the 3- and 12-month period, whereas PIIINP values decreased and PIIICP levels were unchanged in new-onset and chronic DCM, and in pts with and without ECM fibrosis. Both TGF-β and CTGF levels decreased over the observation period. Kinetics of serum markers of collagen synthesis and fibrosis controlling factors did not differ between DCM pts categorized according to disease duration and fibrosis status. Conclusions: The kinetics of collagen type I and III synthesis in DCM move in opposite directions, with production of collagen type I consistently increasing, and the synthesis of collagen type III decreasing. Levels of TGF and CTGF, which are proven fibrosis-stimulating factors, had a tendency to decrease. Regardless of disease duration or fibrosis status, the kinetics of serum markers of collagen synthesis, TGF and CTGF were similar in DCM. A better understanding of the kinetics of serum markers of fibrosis in DCM may help to develop more tailored therapeutic approaches to fibrosis.